The Aussie-FIT process evaluation: feasibility and acceptability of a weight loss intervention for men, delivered in Australian Football League settings. Issue 4 (3rd April 2022) - Kwasnicka, Dominika; Donnachie, Craig; Thøgersen-Ntoumani, Cecilie; Hunt, Kate; Gray, Cindy M.; Ntoumanis, Nikos; McBride, Hannah; McDonald, Matthew D.; Newton, Robert U.; Gucciardi, Daniel F.; Olson, Jenny L.; Wyke, Sally; et al.
Abstract: Objective: This process evaluation aimed to evaluate the feasibility and acceptability of Aussie-FIT, a group-based weight loss intervention for men with overweight and obesity in Australia. Design: Process data and data collected from: (1) six-participant focus groups ( n = 24), (2) coach interviews ( n  = 4), (3) audio recordings of Aussie-FIT sessions and (4) post-program participant surveys ( n = 93) were analysed. Main Outcome Measures: We explored the feasibility and acceptability of program setting and context, recruitment strategies, factors impacting implementation and mechanisms of impact. Results: Recruitment via Australian Football League (AFL) clubs was highly effective; 426 men expressed interest within 3 days of advertising, 130 men took part. Program attendance was not consistently recorded by coaches. Coach interviews indicated a 'core group of men' participated in each session (typically 10–12 of 15 men). Program delivery proved feasible in the AFL context. Program acceptability and satisfaction were high. Internalisation of autonomous motives was identified as driving behaviour change. Behaviour change to support maintained weight loss was facilitated through habit formation, goal setting and effective management of multiple goals. Conclusion: Aussie-FIT sets a blueprint for future weight loss interventions that utilise behaviour change strategies and principles of self-determined motivation to support men to lose weight. Trial Registration: Australian New Zealand Clinical Trials Registry: ACTRN12617000515392. © 2021 Informa UK Limited, trading as Taylor & Francis Group